ATmega8 Microcontroller - Khanji, Tuba Javed; Qureshi, Mohd Ayaz; Shaikh, Shakila (International Journal of Computer Sciences and Engineering, 2019)
A Microcontroller is a tiny computer on a single chip and it is also termed as a control device. Likely to a computer, the Microcontroller is made with a variety of peripherals like i/o units, memory, Timers, serial data communications, programmable. In this article, we will be studying in detail about the Atmega8 microcontroller. It is a low power 8 bit CMOS microcontroller that can execute powerful instructions per clock cycle. It’s small size, low cost and easy availability have helped to become substitutes for PLC controllers, analog circuits, etc. It can be used in embedded applications & automatically controlled devices like remote control devices, control systems, power tools, electronic devices, etc.